2014
DOI: 10.4306/pi.2014.11.1.52
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Ubiquitous Spaced Retrieval-Based Memory Advancement and Rehabilitation Training Program

Abstract: ObjectiveThe Ubiquitous Spaced Retrieval-based Memory Advancement and Rehabilitation Training (USMART) program was developed by transforming the spaced retrieval-based memory training which consisted of 24 face-to-face sessions into a self-administered program with an iPAD app. The objective of this study was to evaluate the feasibility and efficacy of USMART in elderly subjects with mild cognitive impairment (MCI).MethodsFeasibility was evaluated by checking the satisfaction of the participants with a 5-point… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 25 publications
0
43
0
Order By: Relevance
“…For the purposes of our analysis, we considered each article as separate. We found 2 articles that evaluated the ActiveLifestyle app [25,26], AsthmaCare [27,28], EncephalApp [29,30], iMigraine [31,32], iStepLog [33,34], the Mayo Clinic app [35,36], Multiple Sclerosis Performance Test [37,38], My Meal Mate [39,40], Ready~Steady [41,42], a cognitive stimulation app for alcoholics [43,44], USMART [45,46], ClinTouch [47,48], and a food addiction intervention [49,50]. We found 3 articles that evaluated a mobile application in the Women with Epilepsy: Pregnancy Outcomes and Deliveries (WEPOD) study [51-53] and 3 that evaluated the SaGAS 20/10 app [54,55].…”
Section: Resultsmentioning
confidence: 99%
“…For the purposes of our analysis, we considered each article as separate. We found 2 articles that evaluated the ActiveLifestyle app [25,26], AsthmaCare [27,28], EncephalApp [29,30], iMigraine [31,32], iStepLog [33,34], the Mayo Clinic app [35,36], Multiple Sclerosis Performance Test [37,38], My Meal Mate [39,40], Ready~Steady [41,42], a cognitive stimulation app for alcoholics [43,44], USMART [45,46], ClinTouch [47,48], and a food addiction intervention [49,50]. We found 3 articles that evaluated a mobile application in the Women with Epilepsy: Pregnancy Outcomes and Deliveries (WEPOD) study [51-53] and 3 that evaluated the SaGAS 20/10 app [54,55].…”
Section: Resultsmentioning
confidence: 99%
“…Among the phase II participants, 460 subjects from 4 districts (2 rural and 2 urban districts) were followed up as a part of the Korean Longitudinal Study on Cognitive Aging and Dementia (KLOSCAD) [13]. In total, 359 subjects did not meet the criteria for dementia at baseline (i.e., NaSDEK phase II).…”
Section: Methodsmentioning
confidence: 99%
“…In total, 49 studies were retrieved, 11,25-72 comprising 16 reviews 11,25,29,[31][32][33][34][35][36][37][38][39]42,51,60,64 and 33 individual studies. [26][27][28]30,40,41,[43][44][45][46][47][48][49][50][52][53][54][55][56][57][58][59][61][62][63][65][66][67][68][69][70][71][72] Key findings are presented below; more detailed evidence tables are provided in Appendix 1.…”
Section: Objective No 1: Efficacy Of Apps On Chronic Disease Self-mamentioning
confidence: 99%
“…In a review of 24 studies, 64 two RCTs 65,66 and one controlled trial 67 of apps focused on cognitive training showed improved cognition, whereas one RCT did not. 68 Three other RCTs, one of serious games coupled with cognitive training, 69 one with a multicomponent program 70 and another of engagement, 71 showed no effects on various outcomes.…”
Section: Cognitive Impairmentmentioning
confidence: 99%